2015
DOI: 10.1016/j.ejrad.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung abnormalities in treatment-naïve advanced non-small-cell lung cancer patients are associated with shorter survival

Abstract: Objective Interstitial lung diseases are associated with increased risk of lung cancer. The prevalence of ILA at diagnosis of advanced non-small-cell lung cancer (NSCLC) and its impact on overall survival (OS) remain to be investigated. Materials and Method The study included 120 treatment-naïve stage IV NSCLC patients (53 males, 67 females). ILA was scored on CT prior to any systemic therapy using a 4-point scale [0=no evidence of ILA, 1=equivocal for ILA, 2=suspicious for ILA, 3=ILA] by a sequential readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
71
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 27 publications
15
71
1
1
Order By: Relevance
“…It is believed that CT scans may present an overestimation of the comorbidity rate of ILD. The ILD comorbidity rate in our study was 12%, which is comparable to the previously reported incidence of radiographic interstitial abnormality in patients with NSCLC . Considering the higher incidence of comorbidity with ILD in the Japanese population, the incidence of preexisting ILD was reasonable in this study .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is believed that CT scans may present an overestimation of the comorbidity rate of ILD. The ILD comorbidity rate in our study was 12%, which is comparable to the previously reported incidence of radiographic interstitial abnormality in patients with NSCLC . Considering the higher incidence of comorbidity with ILD in the Japanese population, the incidence of preexisting ILD was reasonable in this study .…”
Section: Discussionsupporting
confidence: 84%
“…Patients with interstitial lung disease (ILD) have a twofold higher risk of developing lung cancer than smokers without ILD or chronic obstructive pulmonary disease (COPD) . Lung cancer patients with ILD have few treatment options because surgery, radiotherapy, and chemotherapy elevate the risk of exacerbation of ILD …”
Section: Introductionmentioning
confidence: 99%
“…The precise role of bronchoscopy and bronchoalveolar lavage (BAL) in the management of PD-1 pneumonitis is currently unclear, but BAL may help identify an underlying pulmonary infection. Without biopsy, both patients in the present series lack histologic assessments of pneumonitis, which is often the case with patients who have known advanced malignancy receiving systemic therapy (12, 16). A COP pattern of pneumonitis in the present cases was characterized by the radiographic appearance of the lung abnormalities of pneumonitis, based on the assessment of extent, distribution, and specific CT findings, as described previously (11, 12).…”
Section: Discussionmentioning
confidence: 91%
“…Patients with scores 4 or 5 were considered to be positive for pneumonitis 2, 3 . Radiologists were instructed to disregard the findings indicative of tumoral involvement of the lung 2, 19 . Discrepancies between two readers were resolved by a consensus review of the original two readers (M.N., H.H.)…”
Section: Methodsmentioning
confidence: 99%